A study on microstructural evolution and detwinning behavior of Ti–3Al–2.5V cold-rolled tube during annealing. (30th September 2020) - Yu, Yang; Chen, Rong; Li, Cheng-Lin; Ye, Wenjun; Hui, Songxiao
Abstract: Near alpha titanium alloys have been widely used in the aerospace industry owing to their high special strength, low-density and excellent corrosion resistance. Ti–3Al–2.5V is a typical near alpha titanium alloy that was usually used in the form of a tube in aircraft due to its excellent cold workability. In the present study, the microstructural evolution and detwinning behavior of cold-rolled Ti–3Al–2.5V alloy tubes during annealing were investigated. Upon annealing, the microstructure evolution strongly depends on the annealing temperature and holding time, which play important roles in the kinetics of the static recovery and recrystallization. In addition, there are two independent detwinning mechanisms involved during annealing. The first one is that detwinning occurs along the twin shear direction at grain boundaries, resulting in a shortening effect. The second one is that detwinning occurs in the center of twins, resulting in a thinning effect of twins. The understanding of the detwinning behavior and microstructural evolution during annealing helps with the tube processing and their applications in aircraft.